A least square support vector machine-based approach for contingency classification and ranking in a large power system. Issue 1 (31st December 2016) - Soni, Bhanu Pratap; Saxena, Akash; Gupta, Vikas
Abstract: This paper proposes an effective supervised learning approach for static security assessment of a large power system. Supervised learning approach employs least square support vector machine (LS-SVM) to rank the contingencies and predict the system severity level. The severity of the contingency is measured by two scalar performance indices (PIs): line MVA performance index (PIMVA ) and Voltage-reactive power performance index (PIVQ ). SVM works in two steps. Step I is the estimation of both standard indices (PIMVA and PIVQ ) that is carried out under different operating scenarios and Step II contingency ranking is carried out based on the values of PIs. The effectiveness of the proposed methodology is demonstrated on IEEE 39-bus (New England system). The approach can be beneficial tool which is less time consuming and accurate security assessment and contingency analysis at energy management center.